Customer satisfaction on general banking activities of Shahjalal Islami Bank Ltd.: a study on Mirpur branch - Rahman, A.H.M.Nahid (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration,2014.